Sistem Pencacah Sampah Berbasis Computer Vision Menggunakan Metode Eigenface - Aditya Wijayanto; Alon Jala Tirta; Afifah Dwi Ramadhani (Universitas Budi Darma, 2022)
Indonesia is one of the largest countries in Asia, with a very dense population. According to data from The World Bank, the human population indicator in Indonesia in 2019 increased by 270,625.57 people. It shows that population density in Indonesia is related to world problems related to household waste. The household sector contributes as the top waste producer in Indonesia. Adipura data in 2019 stated that at least household waste contributed 36%. This figure is higher than the heap of waste generated from the traditional market, which reaches 24%. The accumulation of waste that occurs without any sorting of waste makes the waste more difficult to decompose and difficult to recycle. Apart from that, the current landfill causes air pollution. Therefore, it is necessary to increase public awareness regarding waste sorting and processing to overcome these problems. We propose to make a device that can help sort organic and inorganic waste with Artificial Intelligence technology based on Computer Vision using the Eigenface method and the Internet of Things. Eigenface is a method that has the working principle of using an XML file to perform face recognition. 1. Implementation of a Computer Vision-Based Garbage Counting System Using the Eigenface Method can run well, where when the system detects an organic object, the door of the counting machine can be opened, and vice versa if it detects inorganic, the machine door is closed. Accuracy results for organic are 70% and for inorganic 75%. It is due to the lack of variation in the dataset and changes in the object's physical condition.